Cost-Volume-Profit Analysis Untuk Kondisi Uncertainty - Dianawati, Wiwiek (AKRUAL: JURNAL AKUNTANSI, 2010)
AbstrackHotels tend to have a high level of fixed cost owing to the levels of investment required. This should result in above normal profits in good times, as variable costs remaining will form a smaller proportion of additional revenue. However, while high profits can be achieved above the break-even point, high losses will result if revenue is significantly reduced. Thus much attention is given to the traditional CVP model (which ignores uncertainty), as failure to cover fixed costs in the long term can result bankruptcy for organization. This article examines the basic CVP model and describes how to include uncertainty during the decision making process.Key words: CVP model, Break-Even Point, uncertainty